Evaluating the Stratospheric Pathway of the Arctic-Midlatitude Linkage using a Chemistry Climate Model - Schmidt, Franziska (2024)
Arctic amplification is the phenomenon of accelerated warming of the Arctic polar regions in the context of climate change induced by anthropogenic greenhouse gas emissions. A number of recent cold episodes in midlatitudes in winter have raised the question of whether the Arctic amplification has led to the observed midlatitude cooling. The proposed mechanism of this Arctic-midlatitude linkage involves a stratospheric pathway. Accordingly, the horizontal temperature gradients are decreasing due to the enhanced polar warming at the surface. Consequently, the superjacent winds are weakened which results in slower and more meandering polar jet streams. The enhanced planetary waves propagate into the stratosphere, where they induce strong circulation anomalies, referred to as sudden stratospheric warmings (SSWs). These strong disturbances of the stratospheric polar vortex can potentially exert a downward influence on the troposphere, favouring local cold air outbreaks. Investigating this stratospheric pathway in a climate model requires an accurate representation of the middle atmosphere. Therefore, a comprehensive evaluation using the climate-chemistry model ECHAM/MESSy Atmospheric Chemistry (EMAC) was conducted in this thesis, with the additional aim of examining the impact of ozone chemistry on the stratospheric processes. The suggested steps of the stratospheric pathway were examined using a set of transient simulations and timeslice experiments. Although the Arctic amplification signal continued to rise, no cooling trend or cessation of warming was found in the transient simulations. In contrast, the frequency of SSWs has increased significantly under the influence of climate change. This increase could be attributed to a larger planetary wave input from the troposphere. The primary area of enhanced planetary wave propagation was identified as the Northern Pacific and the region spanning the North Atlantic and Europe. Moreover, the number of events corresponding to strong wave input into the stratosphere ...